5 Associations of maternal type 1 diabetes with childhood adiposity and metabolic health in the offspring. (18th March 2018) - Pitchika, Anitha; Jolink, Manja; Winkler, Christiane; Krumsiek, Jan; Kastenmüller, Gabi; Raab, Jennifer; Kordonouri, Olga; Ziegler, Anette-Gabriele; Beyerlein, Andreas
Abstract : Background/aim: Exposure to the intrauterine hyperglycemic environment has been suggested to increase the offspring's later overweight and metabolic risk, but conclusive evidence for pregnancies affected by maternal type 1 diabetes (T1D) is still lacking. Further, it is unknown whether changes in the offspring's metabolome are in the potential pathway. Methods: We analysed data from 610 and 2169 offspring having a first-degree relative with T1D from the TEENDIAB and BABYDIAB/BABYDIET cohorts, respectively. Associations of maternal T1D with anthropometric and metabolic outcomes in the offspring, assessed longitudinally at 0.3–18 years of age, were investigated using mixed regression models. Non-targeted metabolomics measurements were carried out in 500 fasting serum samples from TEENDIAB and associated with maternal T1D and offspring overweight. Results: Offspring of T1D mothers had a higher body mass index standard deviation score (SDS) and an increased risk for overweight than offspring of non-diabetic mothers (e.g. odds ratio for overweight in TEENDIAB: 2.40 (95% confidence interval: 1.41; 4.06)). Further, waist circumference SDS, fasting levels of insulin and C-peptide, as well as insulin resistance and abdominal obesity were significantly increased in offspring of T1D mothers, even when adjusted for potential confounders and birth weight. Metabolite patterns related to androgenic steroids and branched-chain amino acids were found to be associated with offspring's overweight, but no significant associations were observed between maternal T1D and metabolite concentrations in the offspring. Conclusion: Maternal T1D is associated with offspring's overweight and metabolic health in later life, but this is not likely due to alterations in the offspring's metabolome.